ECG review and electrical therapy - Phalen, Tim, 1960-; Fowler, Raymond; Pennington, Jeff; MosbyJems (Firm) (St. Louis : MosbyJems, 2003)
Discusses basic electrophysiology, anatomy of the heart's electrical system, ECG rhythms, 12-lead ECGs, and electrical interventions used in the management of unstable patients, including vagal maneuvers, defibrillation, synchronized cardioversion, and transcutaneous pacing
Presenters, Tim Phalen, Raymond Fowler, Jeff Pennington
VHS
Keywords: Electric Countershock; Electrocardiography; Electrophysiology